Penggunaan Bahasa Jurnalistik pada Naskah Berita (Analisis Wacana Naskah Berita Kesehatan Bulletin RRI Pro1 Bengkulu Periode Bulan September 2023) - Dwi Ningtyas Arum Pertiwi; Mas Agus Firmansyah; Evi Hafizah (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The use of language in making news is called journalistic language, namely language that is easy to understand and not complicated. One of the mass media that presents news is radio, until now Radio Republik Indonesia still exists as a government-owned public broadcasting institution. The news presented on radio is fleeting news, it cannot be played back, so the language used in making radio news must comply with journalistic language rules. The aim of this research is to determine the language used in Bulletin news presented by RRI Pro 1 Bengkulu and to analyze the extent to which the language used is in accordance with objective journalistic rules and can be well understood by listeners. The formulation of the problem raised is how journalistic language is used in health news presented in the RRI Pro 1 Bengkulu Bulletin. This research uses a qualitative approach with discourse analysis methods and uses theories of journalistic language and news. The results of this research are that the language used in the RRI Bengkulu Bulletin Pro1 health news script is guided by the rules of journalistic language writing and EYD, however in the health news script there are still several errors in word usage such as (1) Using abbreviations that are rarely heard by listeners. (2) There are non-standard words (3) Waste of words (4) Use of terms.